Accurate Sex Identification of Ancient Elephant and Other Animal Remains Using Low-Coverage DNA Shotgun Sequencing Data. Issue 4 (1st April 2020) - de Flamingh, Alida; Coutu, Ashley; Roca, Alfred L; Malhi, Ripan S
Abstract: Sex identification of ancient animal biological remains can benefit our understanding of historical population structure, demography and social behavior. Traditional methods for sex identification ( e.g., osteological and morphometric comparisons) may be ineffective when animal remains are not well preserved, when sex distinguishing characteristics have not yet developed, or where organisms do not exhibit sex-associated phenotypic dimorphisms. Here we adapt a method developed for human sex determination so that it can be used to identify the sex of ancient and modern animal taxa. The method identifies sex by calculating the ratio of DNA reads aligning to the X chromosome to DNA reads aligning to autosomes (termed the Rx ratio). We tested the accuracy of this method using low coverage genomes from 15 modern elephants ( Loxodonta africana ) for which sex was known. We then applied this method to ancient elephant ivory samples for which sex was unknown, and describe how this method can be further adapted to the genomes of other taxa. This method may be especially useful when only low-coverage genomic data are obtainable. Furthermore, because this method relies on only the X and not the Y chromosome, it can be used to determine the sex of organisms for which a reference genome was obtained from a female or for which only the X chromosome is reported. Such taxa include the domestic cat, sheep, goat, and horse; and non-domesticated animals such as the Sumatran orangutan, western lowland gorilla and meerkat.